The Relationships Among Periodontitis, Pneumonia and COVID-19 - Brock, Mikaela; Bahammam, Shaima; Sima, Corneliu (Frontiers in Oral Health, 2022)
Periodontitis is a chronic inflammatory disease of the supporting structures of the teeth that affects approximately half of adults 30 years and older. There is increasing interest in the direct and indirect relationships between periodontitis and systemic diseases, including respiratory diseases. The aim of this study was to assess the evidence on links among periodontitis, pneumonia and COVID-19. Oral and periodontal bacteria may be linked to respiratory disease directly by aspiration of pathogens into the lungs causing pneumonia. As SARS-CoV-2 began to spread worldwide in 2020, questions have arisen of how periodontal disease may also be connected to SARS-CoV-2 infection and severity, including potential replication and dissemination of the virus from periodontal pockets. Some proposed mechanisms include the oral cavity acting as a reservoir or point of entry for SARS-CoV-2, overgrowth of periodontal pathogens, and increased production of proinflammatory cytokines. Due to potential links between periodontal disease and respiratory infections like pneumonia and SARS-CoV-2, oral hygiene and management of periodontitis remain essential to help reduce infection and transmission of SARS-CoV-2.